The Cave of the Nymphs at Pharsalus : studies on a Thessalian country shrine - Wagman, Robert S. (Brill Studies in Greek and Roman Epigraphy, 2015)
Cave of the Nymphs at Pharsalus is the first book-length study of one of Greece's most cited nymph sanctuaries. The volume includes a revised catalog, extensive new commentaries on the cave's famous inscriptions, and a first-time investigation of the site's topographical and archaeological layout. Also known as Alogopati or Karapla cave, the Pharsalian shrine holds a special place among ancient nymph caves as the only such site to feature an inscribed poetic chronicle of the shrine's foundation and its founder, the mysterious nymph worshipper Pantalces. Based on years of fieldwork and archival research, Cave of the Nymphs challenges some commonly held views about the origin of this rock-cut 'tale' and offers a fresh perspective for understanding the Pharsalian cave in its proper historical context.